Health Status in Informal Urban Settlements of Barishal, Bangladesh: Social Determinants, Environmental Risks, and Treatment‐Seeking Behavior as Structural Drivers - Md. Ohidur Zaman; Farjana Afroz; Nahida Sultana; Dipti Ranjan Sahu (Health Science Reports, 2026)
ABSTRACT Background Rapid urbanization in low‐ and middle‐income countries has intensified health inequalities within informal settlements, yet empirical analyses often isolate behavioral factors from structural determinants. In Bangladesh, unplanned urban growth has produced vulnerable settlements where social inequalities intersect with infrastructural deficits, particularly in secondary coastal cities such as Barishal, a climate‐sensitive region characterized by migration, poverty, and weak municipal capacity. Aim This study examines the socio‐demographic and socioeconomic patterning of self‐reported health status among households residing in informal settlements in Barishal, Bangladesh, and assesses whether treatment‐seeking behavior independently influences health outcomes or whether structural determinants play a more significant role. Methods A cross‐sectional quantitative research design was employed with 151 households selected through systematic random sampling from the Palashpur informal settlement under the Barishal City Corporation. Data were collected through face‐to‐face structured interviews using a pre‐tested questionnaire. Health status was measured using the Veterans RAND 12‐item composite index. Drawing on the Social Determinants of Health framework, we analyzed the effects of age, gender, education, income, household size, and treatment‐seeking behavior using correlation and multiple linear regression models. Results The regression model explains 46.3% of the variance in health status (adjusted R 2 = 0.444, p < 0.001). Age emerges as the strongest predictor ( β = −0.567, p < 0.001), followed by years of schooling ( β = 0.213, p = 0.002) and household income ( β = 0.159, p = 0.015). Gender becomes significant after controlling for structural variables ( β = −0.197, p = 0.005), while treatment‐seeking behavior shows no independent association with health status. Environmental assessment revealed severe infrastructural deprivation: 62.3% share water sources with over 20 households, 88.7% share latrines with 10 or more households, 76.2% report poor or no drainage, and 90.1% receive no municipal waste collection. Conclusion Findings indicate that health disparities in informal settlements are primarily structured by demographic positioning and socioeconomic resources rather than individual treatment choices. The study contributes localized evidence from a secondary coastal city and underscores the centrality of structural determinants in shaping urban health inequalities.